KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA SEKOLAH - E. LUTFIA ZAHRA (Universitas Negeri Jakarta, 2013)
The objective of this research is to a deep understanding of the management unit production in SMKN 6 Yogyakarta from July 2011 to July 2012. This research is a qualitative with case study method.The validity of the data obtained through the extension of time doing research and triangulation of data collection techniques and data sources in the field. This study concluded are (1) The principal spirited entrepreneurship in managing production units such as visionary, innovative, creative, take advantage of opportunities and courageous in making decisions. (2) The principals delegate authority to the head of the production unit and manager of Edotel through the selection of which is determined by the school principal and submit entirely to the management of the head production unit by study program through the center of Head of Production Unit, except principals Edotel as general manager. (3) In managing the production unit, the principal form of teamwork coordination and communication by the central Head of Production Unit fully devolved to the chairman of the chief study program by joint and has a connection or integration between existing production units in SMKN 6.